(untitled) (Collection of research papers «PROGRESSIVE TECHNIQUE AND TECHNOLOGIES OF FOOD PRODUCTION ENTERPRISES, CATERING BUSINESS AND TRADE», 2026)
Conductive frying is an intensive method of heat treatment widely used in food processing. Heat is transferred directly from heated surfaces to the product which provides rapid heating and the formation of desirable sensory properties of the finished product. Traditional frying processes usually involve relatively high surface temperatures. Such conditions may increase moisture losses reduce product yield and promote the formation of undesirable thermal degradation compounds. Therefore the development of technological solutions that allow a reduction of frying temperature while maintaining sufficient heat transfer intensity is an important task of food technology. The aim of the study was to determine the influence of heating surface temperature and compression pressure on the duration of conductive frying and the yield of minced meat products. The objectives included experimental investigation of the frying process development of mathematical models describing the influence of technological parameters and determination of rational operating conditions. Experimental studies were carried out using a laboratory contact heating unit designed for conductive heat transfer processes. Minced meat samples were fried between heated metal plates at surface temperatures of 120–140 °C and compression pressures of 3–7 kPa. The initial temperature of the samples was 5 °C. The end of the frying process was determined by reaching a temperature of 72 °C in the geometric center of the product. The experimental design was based on a second-order factorial design. Regression analysis was used to obtain mathematical models and response surfaces describing the influence of the studied factors. The results showed that the frying duration significantly depends on both heating surface temperature and compression pressure. Increasing the temperature from 120 to 140 °C reduced the process duration by approximately 35%. Increasing compression pressure from 3 to 7 kPa additionally reduced frying time by about 20%. Mathematical models describing the duration of the frying process and the yield of the finished product were obtained. Response surfaces were constructed to analyze the combined influence of the studied factors. The maximum product yield reached 0.91. Quality evaluation demonstrated improved sensory characteristics higher moisture content and lower shear force compared with products fried using the traditional pan-frying method. The obtained results confirm that increased compression pressure improves thermal contact between the product and heating surfaces and intensifies conductive heat transfer. The rational operating mode corresponds to a heating surface temperature of 140 °C and a compression pressure of 7 kPa which ensures minimal processing time maximum product yield and high quality of the finished product.